SEED PRODUCTION FEASIBILITY STUDY ON SELECTED APPROVED RICE (Oryza sativa L.) HYBRID VARIETIES (Bangladesh Journal of Plant Breeding and Genetics, 2015)
The seed production feasibility of approved hybrid varieties of rice were assessed using 15 commercially approved varieties comprising four public hybrids. Higher seed yield potentiality and earliness in maturity were the two most important indicators for popularizing hybrid rice variety in Bangladesh. The field performance of the approved hybrid rice varieties were found to vary significantly for different traits. Maximum outcrossing potential was observed in SL08HA followed by BRRI hybrid dhan2A but F1 seed yield per plant was the highest in BRRI hybrid dhan3A due to its high tillering ability followed by BRRI hybrid dhan2A, ACI1A and Heera2A. Among the tested entries F1 seed production potentiality of BRRI hybrid dhan3A was maximum indicated its commercial prospect of large scale seed production. Public bred hybrid BRRI hybrid dhan3 and BRRI hybrid dhan2 has immense potentiality for large scale commercialization but BRRI should ensure the quality of parental lines seed as well as supply sufficient amount of seeds according to the demand. Private company hybrids ACI1H and Heera2H have good commercial prospects but seed production under Bangladesh conditions needs to be fine tune.